2016
DOI: 10.2217/pgs-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Atorvastatin Plasmatic Concentrations in Healthy Volunteers Using Integrated Pharmacogenetics Sequencing

Abstract: An integrated analysis of several genes known to intervene in the different steps of metabolism is required to predict atorvastatin's AUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…However, there is little information about the role of CYP2D6 in ATV metabolism or pharmacokinetics. In a previous study, CYP2D6-rs1135840 seemed to have a significant effect on AUC values 13 , but this finding was not confirmed in this study. Here, we identified that CYP2D6-rs1135840 has a significant effect on Ke and T 1/2 parameters, but this was not confirmed with the regression analyses, so its effect on the metabolism and excretion phases is not clear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, there is little information about the role of CYP2D6 in ATV metabolism or pharmacokinetics. In a previous study, CYP2D6-rs1135840 seemed to have a significant effect on AUC values 13 , but this finding was not confirmed in this study. Here, we identified that CYP2D6-rs1135840 has a significant effect on Ke and T 1/2 parameters, but this was not confirmed with the regression analyses, so its effect on the metabolism and excretion phases is not clear.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, synergistic or antagonistic interactions with other gene variants may create variability. So far, evidence on synergistic or antagonistic effect of ABCB1 on ATV plasma concentrations is scarce 13 .The significantly lower values in C/C carriers and the dominant effect of allele T suggest that the rs1045642 polymorphism significantly affects the absorption, bioavailability and blood concentrations of ATV. This hypothesis is supported by the intestinal expression of ABCB1, where this transporter actively participates in drug absorption 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of these biomarkers in future studies may improve the prediction of the pharmacokinetic variability of ATV or decrease the number of variants required for prediction (7,11). While the current study demonstrated the contribution of genetic polymorphisms to ATV pharmacokinetics, there were a number of limitations.…”
Section: Discussionmentioning
confidence: 82%
“…This reflects the underlying variability in the absorption, distribution, metabolism and excretion (ADME) processes of ATV, which may affect the pharmacological response (8). Although in general, genetic factors influence ~30% of variation in drug disposition and response (9,10), recent results have indicated that genetic variability may contribute to >90% of the variance in ATV plasma concentrations (11). These differences in the ADME characteristics of ATV have been attributed to polymorphisms in genes associated with drug pharmacokinetics, particularly those encoding enzymes and transporters (7,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…We identified a new variant on CYP2D8P POS.42547668, 26 Kbp upstream CYP2D6 , and although there is no xenobiotic metabolism reported for this pseudogene, we can speculate that this variant is in LD with another one affecting gene expression or drug metabolism. The inclusion of many variants to dissect a pharmacogenetic phenotype is becoming more common as it increases our knowledge in paths and network interactions not previously considered (Cruz-Correa et al, 2017 ; Oliveira-Paula et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%